Early post-traumatic osteoarthritis-like changes in human articular cartilage following rupture of the anterior cruciate ligament - Nelson, F.; Billinghurst, R.C.; Pidoux, I.; Reiner, A.; Langworthy, M.; McDermott, M.; Malogne, T.; Sitler, D.F.; Kilambi, N.R.; Lenczner, E.; Poole, A.R. (Osteoarthritis and cartilage, 2006)
Injury to the anterior cruciate ligament (ACL) frequently leads to post-traumatic osteoarthritis (OA). In this study we determined whether early degenerative changes characteristic of idiopathic OA are induced in articular cartilage following ACL injury. A small sample of femoral articular cartilage was removed at surgery, as part of ACL reconstruction, from a total of 50 patients with ACL injuries. Of these, 28 underwent surgery less than 1 year post-injury. Control cartilages were obtained from the same site from 21 persons at autopsy. All cartilages were examined for molecular changes. The content of type II collagen, its cleavage by collagenases and its denaturation were determined by immunoassay. The total content of glycosaminoglycan (GAG), which is principally aggrecan, was measured colorimetrically. Data were expressed per unit DNA (GAG and collagen content) or as a percentage of total collagen cleaved or denatured. Other cartilages from the same site (8 controls, 12 less than 1 year and 8 more than 1 year post-injury) were frozen sectioned and examined histologically to determine by Mankin grading cartilage degeneration. Histological analyses revealed that control subjects exhibited staining for proteoglycan, which was reduced in some patients following ACL rupture. Degeneration of the articular surface was sometimes observed 1 year after ACL rupture. Although the Mankin grade increased with time after rupture these changes were not significant. Immunoassays, however, revealed an increase in GAG content within 1 year which was maintained after 1 year although no longer significant. No changes in total type II collagen content were observed during the period of study. However, there were significant increases in the denaturation and cleavage of type II collagen less than and more than 1 year post-ACL rupture. Total type II collagen content was directly correlated with GAG content in all three groups, with the significance being weakest at more than 1 year. After 1 year an inverse correlation was observed between total type II collagen content and collagen cleavage as well as denaturation. These observations reveal that joint instability resulting from ACL injury rapidly results in degenerative changes characteristic of those seen in idiopathic OA at arthroplasty and in experimental OA following ACL surgery. These changes may contribute to the development of post-traumatic OA that is commonly observed following ACL injury. The observations support and extend conclusions from other studies on human and animal articular cartilage and synovial fluids post-ACL injury that have revealed a rapid onset of damage to type II collagen and an initial increase in proteoglycan content characteristic of experimental OA post-ACL injury. This study provides direct evidence for the rapid development of degenerative changes characteristic of OA following ACL injury.